2021
DOI: 10.3389/fmicb.2021.613077
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Organosulfur Compounds of Garlic (Allium sativum)

Abstract: Garlic (Allium sativum), a popular food spice and flavoring agent, has also been used traditionally to treat various ailments especially bacterial infections for centuries in various cultures around the world. The principal phytochemicals that exhibit antibacterial activity are oil-soluble organosulfur compounds that include allicin, ajoenes, and allyl sulfides. The organosulfur compounds of garlic exhibit a range of antibacterial properties such as bactericidal, antibiofilm, antitoxin, and anti-quorum sensing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(131 citation statements)
references
References 160 publications
5
123
1
2
Order By: Relevance
“…As a result, we had no choice but to compare it to the anti-QS effects of active metabolites obtained from other plants. In the last decades, garlic oil, aqueous and solvent (methanol and ethanol) extracts, and sulfur-containing components of garlic have been extensively studied for their antibacterial actions, as well as anti-quorum sensing and anti-virulence properties ( Lee et al, 2012 ; Bhatwalkar et al, 2021 ). The literature shows that sulfur-containing compounds like allicin, ajoene, diallyl trisulfide, and diallyl disulfide form disulfide bonds with free sulfhydryl groups of proteins/enzymes and affect the integrity of the cell membrane or cell wall of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we had no choice but to compare it to the anti-QS effects of active metabolites obtained from other plants. In the last decades, garlic oil, aqueous and solvent (methanol and ethanol) extracts, and sulfur-containing components of garlic have been extensively studied for their antibacterial actions, as well as anti-quorum sensing and anti-virulence properties ( Lee et al, 2012 ; Bhatwalkar et al, 2021 ). The literature shows that sulfur-containing compounds like allicin, ajoene, diallyl trisulfide, and diallyl disulfide form disulfide bonds with free sulfhydryl groups of proteins/enzymes and affect the integrity of the cell membrane or cell wall of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Organosulfur compounds: Organosulfur compounds derived from garlic (Allium sativum) such as allicin, ajoenes and diallyl sulphide, have shown antimicrobial activity against a vast range of pathogens [161][162][163]. These compounds also have been tested as antimicrobial wash for poultry meat to reduce the number of C. jejuni cells [81,82,163].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…Organosulfur compounds: Organosulfur compounds derived from garlic (Allium sativum) such as allicin, ajoenes and diallyl sulphide, have shown antimicrobial activity against a vast range of pathogens [161][162][163]. These compounds also have been tested as antimicrobial wash for poultry meat to reduce the number of C. jejuni cells [81,82,163]. Organosulfur compounds could be a safer and cheaper alternative to commonly used antimicrobials, such as peracetic acid (PAA), in an effort to reduce contamination during pre-and post-chill carcass and broiler parts treatments [164].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…With the development of low copper and copper-free antifoulants, synthetic and natural biocides have been extensively studied as alternatives to prepare antifouling coating with excellent bactericidal performance (Qian et al, 2007b;Huang et al, 2019;Qian et al, 2019;Yang et al, 2021). Allicin (ALL), as one of the active components of freshly crushed garlic homogenates, has many advantages like broad-spectrum antibacterial effect at low concentrations, anticancer activity, and being less likely to develop bacterial drug resistance (Ankri and Mirelman, 1999;Bhatwalkar et al, 2021;Greef et al, 2021). In addition, Rajaneesh et al demonstrated that garlic and its compounds have a positive effect on human beings by inhibiting reactive oxygen species, radical scavenging, and preventing DNA damage (Cao et al, 2014;Zhang et al, 2020;Bhatwalkar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Allicin (ALL), as one of the active components of freshly crushed garlic homogenates, has many advantages like broad-spectrum antibacterial effect at low concentrations, anticancer activity, and being less likely to develop bacterial drug resistance (Ankri and Mirelman, 1999;Bhatwalkar et al, 2021;Greef et al, 2021). In addition, Rajaneesh et al demonstrated that garlic and its compounds have a positive effect on human beings by inhibiting reactive oxygen species, radical scavenging, and preventing DNA damage (Cao et al, 2014;Zhang et al, 2020;Bhatwalkar et al, 2021). Moreover, Breyer showed that garlic compound (ALL) can eliminate mortality on rainbow trout infected with Aeromonas hydrophila (Breyer, 2013).…”
Section: Introductionmentioning
confidence: 99%